Study of good pharmacy practice in community pharmacy of three districts of Kathmandu valley, Nepal - Shrestha, Rajeev; Ghale, Anish (International Journal of Scientific Reports, 2018)
Background: Medicines are an essential component of health-care services. The community pharmacies have great value in terms of providing medicinal services in developing countries. Good Pharmacy Practice (GPP) assesses whether the medicines are safe, effective, available, and accessible and are used correctly. The objective of the study is to assess the good pharmacy practice among community pharmacy of Kathmandu, Bhaktapur and Lalitpur districts. Methods: This was a cross-sectional prospective study. A quota sampling approach was adopted to sample 94 community pharmacies. Data on the premises, storage, prescription handling and dispensing, pharmacy services and rational use of drug were collected using pre-tested questionnaire. Results: The overall compliance with GPP indicators for Kathmandu, Bhaktapur and Lalitpur districts were found to be 12.81 (55.69%), 11.13 (48.39%) and 12.99 (56.48%). On structure wise study, the GPP compliance was higher in others category (Metropolitan city, Sub-metropolitan city and Municipality) i.e. 13.49 (58.65%) and 11.9 (51.74%) in VDC. The studies showed the declining involvement of pharmacists or pharmacy assistants in community pharmacy for more than eight hours a working day i.e. Lalitpur (65%), Bhaktapur (56%) and Kathmandu (59%). Antibiotic dispensing without prescription was highly practiced in Lalitpur 50% compared to Bhaktapur (44%), Kathmandu (34%). Conclusions: It was found that all districts miserably failed to comply with the standards set by GPP particularly Bhaktapur. Pharmacies seemed to have established their place in the society more as a business entity rather than healthcare establishment.